Sosialisasi dan pelatihan aplikasi Sistem Informasi Data dan Pembayaran Iuran Bulanan warga - Indra Gunawan; Muhammad Sadali; Hamzan Ahmadi; Imam Fathurrahman; Aris Sudianto; Suhartini Suhartini; Lalu Kertawijaya; Mahpuz Mahpuz; Muhammad Wasil; Harianto Harianto; Baiq Andriska Candra Permana (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Apart from being in the general community group, residents are also in a complex residential environment. There are housing complexes for the community in subsidized and commercial housing. The large number of citizen data in one housing complex raises many problems, both harmony problems, and administrative problems. The most fundamental problem is how the system records valid citizens and whether the contribution payment system is accountable, valid, and transparent. The team of lecturers from Hamzanwadi University's Informatics Engineering Study Program is doing this service to help the management of RT 005 Lingkar Pratama build a free application system and collect data from citizens. So, it can help RT administrators record and manage complex residential residents' contributions. The method in this service is carried out in stages, starting with problem data analysis, socialization, and training. The results of this service are in the form of implementing applications that can already be used and assist RT admin officers in managing financial reports and information management of citizen data. Of the fourteen administrators who attended the training, on average, they had mastered the application